The Magsaysay award book of citations - Ramon Magsaysay Award Foundation (Manila Ramon Magsaysay Award Foundation, 2002)
An anthology of the official commendations given to the Ramon Magsaysay awardees from 1958 to 2002. It provides a concise description of the awardees and their work, and give us a glimpse of the political and social milieu within which they have demonstrated "greatness of spirit shown in service to the people" and for which they have been accorded the prestigious Magsaysay award.